Who Cares About Development Outcomes? Market Failures and the Role of the Evaluation Function - Moland Gaarder, Marie; Bartsch, Ulrich (Taylor and Francis, 2015)
Development agencies expend large amounts of money and manpower ostensibly to achieve development outcomes that improve living conditions in developing countries. If development agencies cared only about development outcomes and these were easily observable in a timely manner, development agencies would ‘buy’ the best outcomes they could get for their money. And if someone else could get it for them at a lower cost, they would transfer the funds to this other agency. Unfortunately, outcomes are not easily observable, they often take years to appear, and frequently the ‘shopper’ cares more about being seen shopping than about what ends up in the cart. So how do we go about creating a functioning market for development outcomes? What role can the evaluation function play in helping the process of internalizing development outcomes into the development agencies’ objective functions and thereby aligning incentives with the ultimate goal of improving lives? We present the development business through the lenses of the literature on externalities, principal–agent problems, and decision-making under uncertainty. We also present examples of solutions from multilateral and bilateral development institutions.